Akupresur Menurunkan Tekanan Darah pada Pasien Hipertensi di Puskesmas Gang Kelor Kota Bogor - Agustina Agustina; Susmadi Susmadi; Ita Pursitasari; Eros siti Suryati; Franciscus Xaverius (Journal of Pharmaceutical and Sciences, 2026)
Background: Hypertension remains a significant public health challenge in Indonesia, with a prevalence of 34.11% (approximately 90 million people). West Java Province reports one of the highest national prevalence rates at 39.60%, with 56,411 documented cases in Bogor City alone. Often termed "The Silent Killer," hypertension frequently presents without symptoms yet substantially increases the risk of cardiovascular disease, stroke, renal failure, and other complications. Beyond pharmacological interventions, complementary therapies such as acupressure have gained attention as holistic approaches to blood pressure management. However, evidence regarding its specific efficacy beyond educational interventions remains limited. Objective: This study aims to investigate the effect of acupressure therapy on reducing blood pressure in individuals with hypertension compared to sham acupressure combined with health education. Methods: A quasi-experimental study with pre-test and post-test control group design was conducted from June to October 2024 at Gang Kelor and Pasirmulya Community Health Centers, Bogor City. A total of 60 participants aged 45–65 years were recruited through purposive sampling from the PROLANIS chronic disease management program. The intervention group (n=30) received hypertension education and acupressure therapy targeting seven specific acupoints (GV 20, GB 20, TE 17, LI 4, LR 2, LR 3, and BL 23), while the control group (n=30) received equivalent education with sham acupressure at non-acupoints. Both groups received five sessions over four weeks. Blood pressure measurements were taken at baseline and post-intervention. Data were analyzed using independent samples t-test and paired samples t-test with a significance level of α=0.05. Results: Both groups demonstrated significant reductions in systolic blood pressure (intervention: mean difference=12.07 mmHg, p<0.001; control: mean difference=17.53 mmHg, p<0.001) and diastolic blood pressure (intervention: mean difference=6.47 mmHg, p=0.001; control: mean difference=6.87 mmHg, p<0.001). However, between-group comparisons revealed no statistically significant differences in systolic (p=0.128) or diastolic (p=0.876) pressure reductions. Baseline characteristics were homogeneous across groups, with no significant differences in age, sex, education, occupation, hypertension duration, or medication adherence.Conclusion: While acupressure combined with education effectively reduced blood pressure, the additional effect of specific acupressure points beyond education and sham acupressure was not statistically significant. Educational interventions appear to be the primary driver of blood pressure reduction in this population. Acupressure may be recommended as a complementary self-care intervention, but further research with more rigorous designs—including randomized controlled trials with adequate blinding and longer follow-up periods—is warranted to isolate acupressure's specific therapeutic effects.